Peningkatan Pengetahuan Ibu Tentang Inisiasi Menyusui Dini (IMD) Untuk Keberhasilan Memberikan ASI Eksklusif di Kabupaten Jember - Erna Selviyanti; Ria Chandra Kartika; Dessya Puti Ayu Umbaran; Dina Fitriyah; Yohan Yuanta (Journal of Community Development, 2022)
In 2013, there were 18 provinces whose coverage of early breastfeeding was below the national figure, one of which was East Java. Mother's knowledge from pregnancy to childbirth about IMD is very decisive for the success of exclusive breastfeeding and avoiding the baby from being malnourished. The counseling activity for early breastfeeding initiation at Posyandu Catleya 19 was attended by 22 prospective mothers, 7 pregnant women and 6 breastfeeding mothers. Participants were given a pretest to determine the level of knowledge about early breastfeeding initiation. The activity continued with the presentation of material about early breastfeeding initiation to participants. The community service team also provided modules to participants in easy-to-understand language, followed by discussion and question and answer sessions. The topics that were used as questions by the participants were related to family support in breastfeeding, the fear of pregnant women about breast milk that did not come out when giving birth to a baby and equalizing perceptions regarding the importance of breastfeeding for babies starting with early initiation of breastfeeding for newborns. Based on the evaluation results, there were 20 prospective mothers, 7 pregnant women and 4 breastfeeding mothers with a post test score higher than the pretest score or a total of 88.57%. This shows that there is an increase in knowledge about the importance of early breastfeeding initiation for the success of exclusive breastfeeding to infants.